1999
DOI: 10.1021/bk-1999-0716.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Recyclable Extraction and Recovery of Heavy Metal Ions and Radionuclides from Aqueous Media

Abstract: Scientists involved in the separation of ionic pollutants such as radionuclides or toxic heavy metal ions from water have designed extractants with high selectivities and large capacities. Although there is still room for improvement in these parameters, there is a more urgent need to develop processes that allow the target pollutants to be recovered in a minimal volume of secondary waste and that allow the extractants to be reused (recycled). We have studied redox-active transition-metal -containing extractan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many of these materials have potential applications as heterogeneous catalysis, superconductors, , ionic or electronic conductors, , or reversible battery electrodes. We are currently investigating a new application of these materials in another area: waste remediation. We have reported that Li 1.3 MoS 2 is an effective, selective, and redox-recyclable extractant for the removal of Hg(II) from aqueous solution. Therefore, for our purposes, we are very interested in the mechanism of ion removal.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these materials have potential applications as heterogeneous catalysis, superconductors, , ionic or electronic conductors, , or reversible battery electrodes. We are currently investigating a new application of these materials in another area: waste remediation. We have reported that Li 1.3 MoS 2 is an effective, selective, and redox-recyclable extractant for the removal of Hg(II) from aqueous solution. Therefore, for our purposes, we are very interested in the mechanism of ion removal.…”
Section: Introductionmentioning
confidence: 99%
“…The related compound HEP+NO 3 − [HEP + = 1,1′,3,3′tetrakis(2‐methyl‐2‐hexyl)ferrocenium cation] has been used to selectively extract and recover the related tetrahedral monoanions 99 TcO 4 − and ReO 4 − from aqueous solutions containing up to 100,000 times as much nitrate ion (Chambliss et al, 1999a; Chambliss et al, 1999b; Strauss, 1999; Chambliss et al, 1998; Clark et al, 1996). The ion‐exchange process can readily be seen in Figure 3, which displays IR spectra recorded after 5 and 10 min when the coated probe was immersed in 15 μg/L aqueous ClO 4 − .…”
Section: Resultsmentioning
confidence: 99%
“…The compounds DEC + NO 3 − and HEP + NO 3 − are examples of redox‐recyclable extractants, which are being developed in the authors' laboratory for the efficient removal and recovery from water of weakly hydrated aqueous ions, even in the presence of 10 5 times as much nitrate ion in the aqueous phase (Chambliss et al, 1999a; Chambliss et al, 1999b; Clark et al, 1999, Strauss, 1999; Chambliss et al, 1998; Clark et al, 1996; Clapsaddle et al, unpubl.). The basis of redox‐recyclable extraction and recovery (R 2 ER) is that the neutral extractant, in this case a hydrophobic ferrocene [Fe(Cp′) 2 ], is the deactivated low‐affinity form of the extractant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation